32 & 16 YEARS AGO. (Computer (00189162), 2009)
Several excerpts are presented from articles that appeared in the February issues of 1977 and 1993 including articles on software patents and microprocessor design from the February, 1977 issue, and articles on distributed computing and software development from the February, 1993 issue.